NEDD4 Plays Roles in the Maintenance of Breast Cancer Stem Cell Characteristics - Jeon, Seon-Ae; Kim, Dong Wook; Lee, Da-Bin; Cho, Je-Yoel (Frontiers in Oncology, 2020)
Triple-negative breast cancer (TNBC) is the most aggressive type with poor prognosis among the breast cancers and has a high population of cancer stem cells (CSCs) which are main target to cure and inhibit TNBC. In this study, we examined the role of Neural precursor cell expressed developmentally downregulated protein 4 (NEDD4) in proliferation, migration and CSC characteristics of MDA-MB-231, a TNBC cell line. Interestingly, KM plotter showed that the survival rate of patients with higher expression level of NEDD4 was significantly shorter than patients with lower expression only in relatively aggressive and higher stage (grade 3) breast cancer patients. Knockdown of NEDD4 drastically decreased the proliferation, migration, and mammosphere formation in MDA-MB-231 cells. Proteomic analysis revealed alteration of CSC-related proteins, notably Myc targets stem cell-like signatures, in siNEDD4-treated MDA-MB-231. Immunoassay also showed the expression and activity of breast cancer stem cell markers are decreased in NEDD4-deleted MDA-MB-231. Taken together, these results indicate that NEDD4 is involved in the maintenance of population and characteristics of breast cancer stem cells.